2014
DOI: 10.1007/s12013-014-0246-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors for Vascular Cognitive Impairment in Patients with Cerebral Infarction

Abstract: This study aimed to identify risk factors for vascular cognitive impairment (VCI) in cerebral infarction patients. Associations between VCI and age, gender, blood pressure, lipid levels, glycosylated hemoglobin, atrial fibrillation, tobacco smoking, alcohol consumption, homocysteine (Hcy), and High-Sensitivity C-Reactive Protein (HS-CRP) were evaluated in patients with cerebral infarction (n = 300) using single factor analysis and multivariate logistic regression analysis. By single factor analysis, the age, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Similarly, a review of PSD revealed that age ≥ 65 years was a risk factor for PSD (4).To determine whether there is an age-dependent association between Hcy and cognitive impairment in stroke survivors, we divided the total group into two subgroups, ≥65 and <65 years. As mentioned earlier, an independent association has been reported between Hcy and PSCI with a variable time of outcome assessments from 2 months and up to 3 years after stroke (12)(13)(14). We observed an age difference in the relationship between Hcy levels and cognitive impairment in the post-stroke population.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Similarly, a review of PSD revealed that age ≥ 65 years was a risk factor for PSD (4).To determine whether there is an age-dependent association between Hcy and cognitive impairment in stroke survivors, we divided the total group into two subgroups, ≥65 and <65 years. As mentioned earlier, an independent association has been reported between Hcy and PSCI with a variable time of outcome assessments from 2 months and up to 3 years after stroke (12)(13)(14). We observed an age difference in the relationship between Hcy levels and cognitive impairment in the post-stroke population.…”
Section: Discussionsupporting
confidence: 74%
“…In our study, we also found that moderately raised Hcy (≥12 µmol/L in the total group and >8 µmol/L in the younger age group) increased the risk of cognitive impairment in the post-stroke population, which has not been studied yet. Previous studies only considered Hcy as a continuous variable in analysis and did not explore the graded association between Hcy and PSCI (12)(13)(14). The reference values for plasma Hcy ranged from 5 to 15 µmol/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cognitive impairment might be induced by an elevated Hcy level, which is caused by cerebrovascular disease or increased cortical or hippocampal atrophy. Hcy was reported to be a risk factor for vascular cognitive impairment in patients with cerebral infarction, and also an independent risk factor for MCI in the Xinjiang Uygur population [33,34]. It has been shown that high UA levels might be a risk factor for stroke, and the elevated level of UA was correlated with poor prognosis of stroke [35].…”
Section: Discussionmentioning
confidence: 99%
“…All patients who agreed to participate in our research were arranged with a special nursing process post cerebral infarction. The Montreal Cognitive Assessment (MoCA) was used to evaluate the patients' cognitive function [17], by staff who was blind to the study design. The maximum score of the MoCA test is 30.…”
Section: Patientsmentioning
confidence: 99%